Stimulation Successfully Relieved COVID-19-induced Peripheral Nerve Injury in Left Limbs: A Case Report - Bu, Huilian; Jiao, Pengfei; Wang, Yanping; Li, Xinxin; Huang, Chen; Kong, Cunlong; Fan, Xiaochong (Brazilian Journal of Case Reports, 2026)
Coronavirus disease 2019 (COVID-19) may trigger peripheral nerve injury accompanied by intractable neuropathic pain and limb muscular weakness, which frequently fails standard pharmacotherapy and rehabilitation. Spinal cord stimulation (SCS) is an established neuromodulation modality for neuropathic pain management and peripheral nerve functional repair, yet clinical evidence supporting SCS for COVID-19-associated multiple peripheral neuropathy remains scarce, especially in patients with mild COVID-19 lacking mechanical nerve compression risk factors. A 37-year-old male developed refractory bilateral-distributed left-limb neuropathic pain (VAS:6–9) and left-hand weakness following familial clustered mild COVID-19 infection without prone ventilation or external nerve compression. Electroneurography/electromyography (ENG/EMG) confirmed incomplete demyelinating injury involving left brachial plexus, peroneal nerve and tibial nerve; brachial plexus MRI demonstrated local neural edema with indistinct perineural architecture. Conventional pharmacotherapy, physical rehabilitation and paravertebral nerve block only achieved marginal pain improvement. Combined short-term epidural SCS targeting cervical C5–C7 and thoracic T9–T11 was implanted for a total of 14 days. At discharge, VAS decreased to 3 for left hand and 6 for left foot with partial improvement in hand muscle strength. At 1-month and 3-month outpatient follow-up, pain was well-controlled at VAS=2, left-hand muscle strength recovered substantially, and all prescribed analgesics were completely tapered and discontinued. Short-term combined cervicolumbar SCS represents a safe optional neuromodulation alternative for refractory COVID-19-induced multiple peripheral demyelinating neuropathy unresponsive to routine treatment. This intervention effectively alleviates intractable neuropathic pain, facilitates limb muscle functional recovery and reduces long-term reliance on analgesics. Early SCS trial can be considered as individualized salvage therapy for refractory long-COVID peripheral neurological sequelae.